2004
DOI: 10.1111/j.0736-8046.2004.21513.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pruritic Linear Urticarial Rash, Fever, and Systemic Inflammatory Disease in Five Adolescents: Adult‐Onset Still Disease or Systemic Juvenile Idiopathic Arthritis sine Arthritis?

Abstract: The characteristic rash of systemic juvenile idiopathic arthritis is a transient erythematous eruption associated with a quotidian spiking fever. Usually asymptomatic, it can be pruritic, with dermatographism at sites of scratching or pressure. An illness similar to this entity in adults is designated adult-onset Still disease. The relationship between the pediatric and adult disease is uncertain and differences in case definition have evolved. Specifically, a sustained arthritis for at least 6 weeks is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The three reported cases had atypical cutaneous eruption. Patients 1 and 3 presented persistent urticarial lesions, a rare manifestation previously reported in a few cases [8,[14][15][16][17][18][19][20][21][22]. Patient 2 had urticarial papules and persistent erythema which was aggravated during fever spikes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The three reported cases had atypical cutaneous eruption. Patients 1 and 3 presented persistent urticarial lesions, a rare manifestation previously reported in a few cases [8,[14][15][16][17][18][19][20][21][22]. Patient 2 had urticarial papules and persistent erythema which was aggravated during fever spikes.…”
Section: Discussionmentioning
confidence: 86%
“…However, only about 25 cases of AOSD are described in the literature which had a clinical presentation with urticaria or angioedema [8,[14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] A recent case series demonstrated that it is characterized by necrotic keratinocytes in the mid and upper epidermis, including in the cornified layer. 2 In addition, a separate case report has noted marked diffuse mucinosis, confirmed with Alcian blue staining, that corresponded to similar clinical findings on the upper arms and proximal thighs.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, dermatographism and Köebner phenomenon have been described as objective features of AOSD [5,6,9,19]. Various atypical rashes have been reported in AOSD such as persistent dermal plaques, [20][21][22][23] urticaria [19,24], and vesicolupustular lesions on the hands and feet [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dermatographism could be seen in 1.5-5% of the healthy population [26,27]. Pathogenesis of dermatographism is unclear [19]. It is usually idiopathic, but it may be associated with systemic use of penicillin, famotidin, and atorvastatin [27,28].…”
Section: Discussionmentioning
confidence: 99%